Ahmadi RELIGIOUS TEACHER FORMING CHARACTER SANTRI - Ahmadi, Ahmadi Ahmadi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2020)
Ustadz is a person who has expertise in religious science and has a great role in the world of education, especially in Islamic education in Pondok, Pondok Pesantren. To print a smart, successful general, so much performance for the need for the evaluation of the role of religious teachers in school or pondocketors, such as Pondok Pesantren Nurus Sholah Batu labang Akkor Palenga Pamekasan.This research is an attempt to know how the role of religious teachers in shaping the character of santri in the pondok Pesantren Nurus Sholah. Answering the question, then this research uses a qualitative approach that produces data obtained from the object of research by interview methods, observation and documentation, which then analyzed by describing data from informants, reducing data according to research needs, then analyzed by the author, and concluded to answer. Research, the findings of this study is that: (1) the formation of the character of the santri in the cottage of the Nurus Sholah. Physical Press. The nursing shocks. Together with the Sell of the Yellow Book, train the discipline, self-responsibility and independence implemented inside and outside the class. (2) In the future of the santri character in the cantrant of the Nanty Shochant Pantokt. The role of Pusantren Nurus Sholah. That role of Urdaadz's ascestors, educators, teachers, correctors, advisors, executants, supervisors, in the implementation are found in a number of obstacles, which is lack of teachers, the physical condition of the santri that is tired because in addition to following learning in the cottage also follows learning in schoolguos, lack of facilities and infrastructure while the carrying capacity is a good relationship between teachers and santhanya, In the learning of teachers using a good approach to sufferer for a role of religious teacher to make santri-santri in this lodge is happy to attend the programs that have been made by the management, the cooperation between the Board of Management is also very important in managing and developing education in this cottage to achieve the inhabitants you want to match the vision and mission in this cottage. Based on the results of this study is expected to be the material and input to the Pondok Pesantren Nurus Sholah, caregiver, Ustadz, researchers and all parties in need.